IDENTIFIKASI TEKNIK KONSERVASI TANAH DAN AIR DI DESA TABO-TABO KECAMATAN BUNGORO KABUPATEN PANGKEP - pammu, Wahyuni; Arsyad, Usman; Khaerunnisa, Puteri (Program Studi Kehutanan Universitas Muslim Maros, 2019)
This study aims to identify and to assess the accuracy of soil and water conservation techniques applied by the community in Tabo-Tabo Village, Bungoro District, Pangkep Regency. This research was conducted from June to October 2018. The type of data collected is primary data and secondary data. Primary data was obtained by direct observation in the field in the form of surveys and interviews while secondary data collection was in the form of administrative map from BPS and land use cover map from BPKH. The results of soil and water conservation technique in TaboTabo Village, Bungoro District, Pangkep Regency were 74.3% from 35 farmers in the right category and 25.7% inappropriate category. The conservation technique used by farmers in TaboTabo Village were a vegetative technique in the form of cover crops, mixed gardens, yards and living fences, while mechanical techniques include bench terraces and flat terraces.